2017
DOI: 10.4172/2327-5146.1000287
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Professional Physical Therapists in Smoking Cessation: A Literature Update

Abstract: Objective: To update the literature on the role of the physical therapist in smoking cessation interventions and the effects of smoking in different therapeutic approaches. For this update the Medline, Scielo, Lilacs and Cochrane electronic databases were searched using the following keywords: physical therapy specialty, physical therapists, tobacco use cessation, smoking, national program of tobacco control. The physical therapist presents particularities that enable them a broad role in smoking intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Freire et al 17 demonstrated that physical therapists present particularities and unique characteristics that can become facilitators in the smoking intervention process and, therefore, act not only in prevention, but also in the intervention of the tobacco use disorder cessation process of their patients, besides considering the condition of smoker in the evolution of physical therapeutic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Freire et al 17 demonstrated that physical therapists present particularities and unique characteristics that can become facilitators in the smoking intervention process and, therefore, act not only in prevention, but also in the intervention of the tobacco use disorder cessation process of their patients, besides considering the condition of smoker in the evolution of physical therapeutic treatment.…”
Section: Introductionmentioning
confidence: 99%